Hard ticks and their bacterial endosymbionts (or would be pathogens) - Ahantarig, Arunee; Trinachartvanit, Wachareeporn; Baimai, Visut; Grubhoffer, Libor (Folia microbiologica, 2013)
The symbiotic microorganisms of arthropod vectors are highly significant from several points of view, partly due to their possible roles in the transmission of pathogenic causative agents by blood-sucking vectors. Although ticks are well studied because of their significance to human health, novel microbial associations remain to be described. This review summarises several endosymbiotic bacterial species in hard ticks from various parts of the world, including Coxiella-, Francisella-, Rickettsia- and Arsenophonus-like symbionts as well as Candidatus Midichloria mitochondrii and Wolbachia. New methodologies for the isolation and characterization of tick-associated bacteria will, in turn, encourage new strategies of tick control by studying their endosymbionts.
Keywords: Biodiversity; Bacterial Physiological Phenomena; Symbiosis; fyziologie bakterií; zvířata; Ixodidae; symbióza; Bacteria; biodiverzita; Animals